Apatite alignment and orientation at the Ångstrom and nanometer length scales shed light on the adaptation of dentine to whole tooth mechanical function. Issue 4 (December 2013) - Zaslansky, P.; Maerten, A.; Fratzl, P.
Abstract : Human teeth are capped by a highly mineralized enamel layer that rests on a bone-like material termed dentine. Dentine is composed mainly of collagen and carbonated apatite known to form the biological composite of all types of bone by combining into mineralized collagen fibrils. The apatite mineral is found both within and also encasing the fibrils, but in dentine, particularly in the crown, mineral is also found in regions where there is no collagen, forming peritubular dentine cuffs that surround narrow channels that perforate and render dentine porous. The authors hypothesize that regional variations in the mineral spatial configuration may reflect local adaptation to functional needs of whole teeth. The 3D orientation of the micron-sized tubules and the associated clusters of peritubular mineral vary on the length scale of millimeters. The orientation and degree of coalignment of the nanometer-sized mineral platelets in dentine exhibit marked changes at the same length scale, matching predicted load-trajectories in loaded teeth. However, wide-angle X-ray diffraction mapping shows that there is almost no preferred orientation of the 002 reflection (and hence the c-axis of apatite). The authors thus propose that the orientation of the peritubular and intertubular mineral compensate for localized preferred orientations, to create an overall average, randomly oriented mineral configuration.